Triruthenium-iridium clusters containing alkyne ligands: synthesis, structure, and catalytic implications of [(mu-H)IrRu3(CO)(11)(mu(3)-eta(2)-PhC CPh)] and [IrRu3(CO)(10)(mu(4)-eta(2)-PhC CPh)(mu-eta(2)-PhC = CHPh)] - Ferrand, Vincent; Süss-Fink, Georg; Neels, Antonia; Stoeckli-Evans, Helen (My University, 1998)
The mixed-metal cluster [HIrRu3(CO)(13)] 1 reacts with one equivalent of disubstituted alkynes RC=CR to give [HIrRu3(CO)(11)(mu(3)-eta(2)-RC=CR)] (R = Ph 2; R = Me 3), with a second equivalent of the alkyne the clusters [IrRu3(CO)(10)(mu(4)-eta(2)-RC=CR)(mu-eta(2)-RC=CHR)] (R = Ph 4; R = Me 5) are obtained. The single-crystal X-ray structure analyses of 2 and 3 show these clusters to have a tetrahedral Ru3Ir framework containing the alkyne ligand coordinated in a parallel fashion over the Ru, face of the metal skeleton. In contrast, the clusters 4 and 5 consist of a butterfly arrangement of the Ru3Ir framework with the alkyne ligand coordinated to all four metal atoms, giving an overall octahedral Ru3IrC2 skeleton, as demonstrated by the single-crystal structure analysis of 4. Cluster I,is an excellent catalyst for the hydrogenation of diphenylacetylene to give stilbene (catalytic turnover number 990 within 15 min), clusters 2 and 1 are also catalytically active but seem to represent side-channels of the catalytic cycle.
Keywords: TUNGSTEN TRIOSMIUM FRAMEWORK; CRYSTAL-STRUCTURE; CARBONYL; COORDINATION; SCISSION